Pengaruh Dukungan Keluarga terhadap Eksistensi Komunikasi Teungku Inong di Dunia Digital - Fitri Meliya Sari; Wirdatul Jannah (Jurnal Peurawi: Media Kajian Komunikasi Islam, 2025)
This study aims to identify and analyze the influence of family support on the existence of Teungku Inong, a female preacher, in the digital world. The family support discussed includes emotional, financial, technical support, provision of time and space, as well as religious education and values. The research method used is a qualitative approach with data collection techniques through in-depth interviews and observations. The results show that family support plays a crucial role in Teungku Inong's success in digital preaching. Emotional support provides motivation and confidence, while financial and technical support enables Teungku Inong to produce high-quality content. Furthermore, the provision of flexible time and space, along with religious education within the family, strengthens Teungku Inong's commitment and integrity.